Pengaruh Love Language Terhadap Keharmonisan Pada Pasangan Remaja Di Kota Yogyakarta - Cicilia Levina Putri Jelita; Ryan Apriliano Wijaya; Fallum Falfadiga Syef Afgatan (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2025)
Romantic relationships among adolescents are often influenced by the way they express and receive affection. Understanding love languages ​​is key to strengthening relationships and increasing emotional satisfaction. The purpose of this study was to explore the impact of love languages ​​on the harmony of young couples in Yogyakarta. Through a quantitative survey approach, data were collected from 100 participants aged between 17 and 24 years using a structured questionnaire. The results of the analysis showed that "affirmative words" and "quality time" had a significant relationship with emotional satisfaction and relationship harmony. These findings emphasize the importance of verbal communication and emotional presence in creating healthy relationships. This study also provides insight to adolescents and counselors regarding the dynamics of romantic relationships through the application of the concept of love languages. Recommendations for the development of interpersonal relationship education based on love languages ​​have also been presented.